SEED PRIMING TECHNIQUES MAY IMPROVE GRAIN AND OIL YIELDS OF SUNFLOWER (HELIANTHUS ANNUUS L.) - S. Baser Kouchebagh; F. Farahvash; B. Mirshekari; H. Kazemi Arbat; F. Rahimzadeh Khoei (Journal of Animal and Plant Sciences, 2014)
Seed priming has been reported to enhance growth of plants. To evaluate the effect of some physical seed priming materials (ultrasonic, gamma, beta, laser, magnetic field, irradiations and hydro-priming) on yield and yield components of sunflower, field experiments were conducted at Islamic Azad University, Tabriz branch, Iran during 2011-2012 in a randomized complete block design, with three replications. The results revealed that crop LAI, following pre-sowing treatments, increased by magnetic fields, laser for 5 and 15 min. and ultrasonic up to 3.36, 3.41, 3.91 and 3.53, respectively. Beta and gamma rays, hydropriming and non-priming of seeds reduced it at 70 DAE. Highest mean yield produced from seeds treated with laser (419.7g.m-2) and magnetic field (379.8g.m-2) for 5 min. However, it decreased by increasing laser duration from 5 to 10 min. Biomass produced ranged from 947.4 g.m-2 in seeds primed under laser for 5 minutes. and 406.7 g.m-2 in non-priming ones. It was also found that sunflower seeds irradiated with laser for 5 and 10 minutes and magnetic fields resulted in highest harvest index (49.1%), as compared with other treatments. It may be concluded that sunflower growers could improve crop yield by priming the seeds with magnetic field and laser irradiation before sowing.
Keywords: Magnetic field; Oil percentage; Physical priming